1996
DOI: 10.1111/j.1432-2277.1996.tb00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Graft size-matching in living related partial liver transplantation in relation to tissue oxygenation and metabolic capacity

Abstract: The influence of graft size-matching on tissue oxygenation and metabolic capability was studied in living related partial liver transplantations for 47 pediatric patients. Their age ranged from 4 months to 17 years 3 months, their body weight from 4.0 to 58.0 kg, graft weight from 191 to 440 g, and graft weight/recipient body weight ratio from 0.61% to 6.0%. Tissue oxygenation and its heterogeneity were investigated by measuring oxygen saturation of hemoglobin in the liver sinusoid (SO2), coefficient of variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Consequent to aforementioned physiologic disturbances between the donor and the recipient, metabolic mismatch may contribute to the development of small‐for‐size syndrome. Tanaka et al showed that there is a correlation between graft/recipient size mismatch and bilirubin clearance in post‐transplant day 1. Cholesterol esterification was suppressed compared to preoperative level for 2 weeks in small‐for‐size grafts presumably due to delayed synthesis of acetyltransferase and Apoprotein A1, indicating that graft synthetic function was delayed in small‐for‐size grafts.…”
Section: Consequences Of Size Mismatch In Liver Transplantmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequent to aforementioned physiologic disturbances between the donor and the recipient, metabolic mismatch may contribute to the development of small‐for‐size syndrome. Tanaka et al showed that there is a correlation between graft/recipient size mismatch and bilirubin clearance in post‐transplant day 1. Cholesterol esterification was suppressed compared to preoperative level for 2 weeks in small‐for‐size grafts presumably due to delayed synthesis of acetyltransferase and Apoprotein A1, indicating that graft synthetic function was delayed in small‐for‐size grafts.…”
Section: Consequences Of Size Mismatch In Liver Transplantmentioning
confidence: 99%
“…A large graft receives relatively low portal blood flow due to relatively small recipient body size, which impairs hepatic microcirculation . Rangel Moreira Dde et al showed that using a porcine model significantly lowers portal venous flow with a higher level of lactic acid and arteriovenous pCO 2 difference with lower pH, which represents the lower tissue perfusion, in the large‐for‐size group.…”
Section: Consequences Of Size Mismatch In Liver Transplantmentioning
confidence: 99%
“…It must be accurate, as much as possible, in order to not only guarantee enough graft volume to the recipient but mainly to assure enough residual liver volume to the donor. In general, a graft volume body weight ratio (GVBWR) of 0.8 [43] or 40% of the recipient's standard liver volume [32,44] is recommended as a minimum cut‐off for the recipient, even though successful transplantations have been reported with GVBWR <0.7 [45,46]. The Kyoto group showed a statistically significant correlation between complication, graft loss, and a GVBWR of <0.8 [47].…”
Section: The Donormentioning
confidence: 99%
“…After closure of the abdomen the large for size grafts are prone to compression, which can cause partial liver necrosis or compromise the flow in afferent hepatic vessels and result in thrombosis (40). Two studies from Japan showed that graft oxygenation was lower intraoperatively in oversized grafts and these grafts likely suffered dysoxia (41, 42). Other problems that can arise from too tight abdominal closure because of oversized graft include renal failure and respiratory failure.…”
Section: Discussionmentioning
confidence: 99%